Effects of Tai chi in knee osteoarthritis patients: An overview of systematic reviews and meta-analyses - Naijin Zhang; Huaixing Cui; Hongyu Li; Yuhang Yang; Zhuo Gao; Xianyue Zeng; Xuan Sun; Huaien Bu; Hongwu Wang (Elsevier, 2023)
Objective: Tai Chi (TC) is a complementary therapy for knee osteoarthritis (KOA). Although systematic reviews (SRs) and meta-analyses (Mas) of efficacy studies have been published, the results remain uncertain, and their quality has not yet been fully evaluated. Here, we summarize the existing SRs/Mas, evaluate their quality and level of evidence, and provide a reference for the effectiveness of TC. Methods: SRs/Mas of TC therapy for KOA published before February 2023 were retrieved from eight databases in Chinese and English. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020, and the Risk of Bias in Systematic (ROBIS) scale were used to assess methodological quality, reporting quality, and risk of bias. Results: Seven SRs/Mas were finally included. One was deemed high quality by AMASTAR-2, while the rest were of critically low quality. In the PRISMA2020 assessment, the response rate of "Yes" for Q7, Q15, Q22, Q24, and Q27 was less than 50%. In the ROBIS assessment, three reports in Phase 3 were high risk and four were low risk. In the efficacy assessment, TC has shown varying degrees of improvement in physical function, pain, stiffness, 6-minute walk test, mental quality of life, TUG, and balance in patients with KOA. Conclusion: TC effectively treats KOA-associated pain, stiffness, body function, and mental quality of life. However, the low methodological quality of the studies and the high risk of migration reduced their reliability. Therefore, these conclusions should be taken with caution. High-quality, large-sample research is needed to provide stronger and more scientific evidence.